Compulsive Buying and Personality Traits - Gojković, Vesna; Stevanović, Aleksandra; Milutinović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
People’s tendency to buy compulsively (compulsive buying – CB), which is defined as chronic (repetitive) preoccupation with buying with low impulse control, is still an insufficiently explored psychological problem. In this paper, we tried to predict whether and in which way personality traits, which are defined by Eysenck’s model, can predict this affinity, also whether there are gender differences and differences in financial status compared to the level of expression of CB. We examined a hundred examinees, the same number of males and females, with an average age of 28, from Niš, who were classified in different categories according to their incomes. Besides the questionnaire EPQ 102, which determined the personality profile, the Compulsive Buying Scale KK35 was also used, which was translated from English and modified. High reliability and representativeness of the Compulsive Buying Scale were determined, and four factors were abstracted by factor analysis: social status, immoderation, symptoms of addiction and compulsive desire. Latent content of factors indicated validity of the hypothesis, which says that Compulsive buying is a multi-dimensional construct that consists of clinically defined variables (compulsiveness and addiction), as well as socially defined variables (social status and immoderation). It was found that Neuroticism and Psychoticism significantly predict CB in a way that Neuroticism is expressed through compulsiveness and addiction (clinical dimension), while Psychoticism is expressed through addiction symptoms (clinical dimension) and immoderation (social dimension). Extroversion is not associated with CB. It is confirmed that women have much more preference for CB than men, and the difference is determined by factors: compulsive buying and symptoms of addiction (clinical dimension), which is in relation to a higher level of Neuroticism in women than in men. Financial status is not related to compulsive buying.